Draft Annual Plan 1990-91 Vol-I Introduction and GN Statements - Planning Commission (Planning Commission, 1990)
Keeping in view the remoteness of the State from the States in the mainland, the direction and thrust of the plan has been to make the State self-sufficient and self-reliant in meeting its essential needs — food grains etc., the agriculture and allied sector, therefore, becomes the central thrust area of the Plan. Efforts were being made to ensure that the food production is increased by introducing appropriate technology and other improved inputs in this sector.
Government of Tripura
Government of Tripura